2020
DOI: 10.1002/jls.21695
|View full text |Cite
|
Sign up to set email alerts
|

The Satisfaction and Frustration of Basic Psychological Needs in Engaging Leadership

Abstract: The purpose of the current study was to test engaging leadership, which is a recently developed leadership concept based on basic psychological needs theory. Drawing on self‐determination theory, the current study hypothesized that basic psychological needs mediate the relationship between engaging leadership and both positive and negative outcomes. An association between need satisfaction and positive results and an association between need frustration and adverse outcomes were expected. The survey data, coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 65 publications
3
15
0
Order By: Relevance
“…In other words, satisfaction of the four basic needs should mediate the effect of engaging leadership on work engagement. This indeed appears to be the case, for example among South African miners (Erasmus, 2018 ), employees of Flemish health insurance funds (Robijn et al, 2020 ), office staff of a Dutch insurance company (Robijn, 2021b ), staff of the back office of a Dutch technology company (Van Tuin et al, 2020a ) and finally Russian civil servants and employees working at an Indonesian palm oil plantation (Rahmadani et al, 2019 ). In all cases full mediation was observed, except for Russian civil servants and Dutch back-office staff, where the mediation was partial in nature.…”
Section: Empirical Research On Engaging Leadershipmentioning
confidence: 99%
“…In other words, satisfaction of the four basic needs should mediate the effect of engaging leadership on work engagement. This indeed appears to be the case, for example among South African miners (Erasmus, 2018 ), employees of Flemish health insurance funds (Robijn et al, 2020 ), office staff of a Dutch insurance company (Robijn, 2021b ), staff of the back office of a Dutch technology company (Van Tuin et al, 2020a ) and finally Russian civil servants and employees working at an Indonesian palm oil plantation (Rahmadani et al, 2019 ). In all cases full mediation was observed, except for Russian civil servants and Dutch back-office staff, where the mediation was partial in nature.…”
Section: Empirical Research On Engaging Leadershipmentioning
confidence: 99%
“…The respondents of study 2 were engineers overseeing complex mass‐production processes, whereas the respondents in study 1 were business information analysts and order‐managers.Despite its firm roots in a well‐established theory of human motivation, the measure of EL is relatively new and cannot draw on a wealth of studies. Nevertheless, a growing body of research has been conducted, under which: a diary study investigating the impact of EL on daily team job‐crafting (Mäkikangas et al, 2017); a crossed and lagged panel study into the relationships with autonomy, social support, learning opportunities, and engagement (Nikolova et al, 2019); mediational analyses on the role of basic psychological needs satisfaction (Rahmadani et al, 2019) and needs frustration (van Tuin, Schaufeli, & Van Rhenen, 2020); an intervention study on the impact on business results and well‐being (van Tuin, Schaufeli, Van Rhenen, & Kuiper, 2020). Another aspect is the more general issue of construct proliferation in leadership research (Shaffer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on EL indicated an indirect effect on burnout and engagement via job demands and resources, as well as a direct impact on employability, performance, and commitment (Schaufeli, 2015). Later studies showed a positive association of EL with work engagement through the satisfaction of the basic psychological needs (Rahmadani et al, 2019) and their frustration (van Tuin, Schaufeli, & Van Rhenen, 2020), as well as positive effects on employee learning and innovative job behavior (Rahmadani et al, 2020), team job crafting (Mäkikangas et al, 2017), autonomy satisfaction, and social support (Nikolova et al, 2019). Additionally, a recent leadership intervention study showed that training managers in EL behaviors led to improved business results, lower absenteeism, and well‐being (van Tuin, Schaufeli, Van Rhenen, & Kuiper, 2020).…”
Section: Engaging Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Leadership has been studied from myriad perspectives, including evolutionary theories (Van Vugt et al, 2008), popular culture (Kuri and Kaufman, 2020), psychology (Tuin et al, 2020), traits (Gardner, 1989;Zaccaro, 2007), and import of trust (Braun et al, 2013;Torres and Bligh, 2012), or empowerment (Avolio et al, 2004), leader-member exchange (Schyns, 2013;Yukl et al, 2013), sincerity or authenticity (George, 2003), and power (Collinson, 2005;Burns, 1979), or as a social process as opposed to individual action (Bolden, 2011;Bennett et al, 2003) to name just a few. And while leadership has been traditionally studied from a Western cultural perspective, there is now a growing trend to look at other regional (Chong and Fu, 2020;Ma and Tsui, 2015) and global perspectives (Hanges et al, 2016).…”
mentioning
confidence: 99%